Preparation of AZ91D Magnesium Alloy Superhydrophobic Surface Based on Silanization Pretreatment by Spraying Method - ZHANG Yong - jun, YAN Ge (Cailiao Baohu, 2021)
In order to improve the corrosion resistance of magnesium alloy and push magnesium resource utilization, with static contact angle, bonding force, and corrosion resistance as the main technical indicators, a two - step spray coating treatment technology for superhydrophobicization of magnesium alloy surfaces was successfully developed. The optimal coating formula: 2 g/L CNTs, 1 g/L SiC, 40 mL/L TEOS, 0.2 mL/L FAS, ethanol as solvent. The optimal coating process: the substrate was sprayed with KH560 hydrolysate as the binder, the volume/sample area ratio was controlled to 4 L/m2 for the first time spraying as pretreatment, and the coating volume/sample area ratio was controlled to 18 L/m2 for the secondary spraying, drying at 120 ℃ × 2 h. For typical samples, the coating/substrate bonding force was evaluated by the cross - cut method, the microscopic morphology of the coating surface and section was analyzed by SEM, the corrosion resistance was studied by the drop test. Results showed that the superhydrophobic coating had a micro /nano graded structure, and the static contact angle with deionized water droplets reached 154.5°. In addition, the binding force could reach 5B level, and the drip time was extended by 17 times.